Analisis Konsep Partisipasi Masyarakat Terhadap Substansi Pengaturan Dan Problem Yuridis Dalam Undang-Undang Nomor 7 Tahun 2017 Tentang Pemilihan Umum - Alma Putri Salsabila; Aswaja Shinta Fadhilah; Rima Nur Lailatul Fitriani; Pulung Sari Tri Arsiyanto; Dini Fitriani (Fakultas Hukum, UPN Veteran Jawa Timur, 2020)
This study examines the role of public participation in general elections as stipulated in Law Number 7 of 2017. Although the law recognizes the importance of public involvement, its provisions remain normative and do not provide clear operational mechanisms, resulting in conceptual ambiguity, weak legal protection, and barriers to substantive public involvement. The results of the study indicate that legal problems such as a lack of implementation standards, overlapping authority, limited access to information, and vulnerability of reporters impact the low effectiveness of public participation. Furthermore, political dynamics and structural challenges such as inequality in political literacy, the practice of money politics, and uneven infrastructure contribute to the deterioration of public participation in elections. Therefore, strengthening public participation requires regulatory updates, expanded access to information, stronger legal protection, and structural reforms so that the public can play a role as active observers and not merely passive voters.